2006
DOI: 10.1002/cncr.21873
|View full text |Cite
|
Sign up to set email alerts
|

Impact of estrogen receptor expression and other clinicopathologic features on tamoxifen use in ductal carcinoma in situ

Abstract: The iterated unscented Kalman filter (IUKF) is a promising nonlinear tracking algorithm. However, we find that the IUKF has poor performance in tracking accuracy and will diverge easily when the variance of observation noise is large, because the iterated state prediction is nonorthogonal to the current observation after the first iteration. This will increase the proportion of current observation in state estimate and lead to the tendency for the final iteration result to be closer to the observation compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Results from the Breast and Bowel Project B‐24 trial demonstrated that adding tamoxifen to BCS and radiation significantly reduced risk of invasive breast cancer compared with BCS and radiation alone , though a later reanalysis indicated that the benefit of tamoxifen was limited to those with ER+ DCIS . These findings have contributed to an increase in the ER testing of DCIS tumors, now routine in many institutions . In our cohort of DCIS patients diagnosed between 2006 and 2010, HR status was available for over 80% of women, with HR+ disease predictive of endocrine therapy initiation.…”
Section: Discussionmentioning
confidence: 91%
“…Results from the Breast and Bowel Project B‐24 trial demonstrated that adding tamoxifen to BCS and radiation significantly reduced risk of invasive breast cancer compared with BCS and radiation alone , though a later reanalysis indicated that the benefit of tamoxifen was limited to those with ER+ DCIS . These findings have contributed to an increase in the ER testing of DCIS tumors, now routine in many institutions . In our cohort of DCIS patients diagnosed between 2006 and 2010, HR status was available for over 80% of women, with HR+ disease predictive of endocrine therapy initiation.…”
Section: Discussionmentioning
confidence: 91%
“…Prospective data is mixed regarding the magnitude of the benefit of tamoxifen in the setting of DCIS. Receptor expression is important in DCIS for predicting the patients who will benefit from the addition of tamoxifen in the adjuvant setting (10, 3739). Estrogen receptors (ER) are highly expressed in 50–60% of patients with DCIS.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of ER expression are higher in DCIS lesions with less aggressive histologic features, such as low grade, increasing differentiation and absence of necrosis, than in those with more aggressive features (13). In 2003, the St Gallen International Consensus Panel endorsed the use of tamoxifen in hormone- receptor positive DCIS (40) and the role of tamoxifen has been evaluated in different series (10, 11, 13, 31, 38, 39, 41). The use of tamoxifen has increased from 24% to 46% in a study by Yen (11) et al before and after the year 1999.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with three prior single-institution studies of patterns of care for DCIS, which all demonstrated that BCS was an independent predictor of tamoxifen use. [9][10][11] Thus it appears that physicians are using tamoxifen in this setting with true adjuvant intent, and not simply as chemoprevention for the contralateral breast. The fact that physicians do so selectively in women younger than age 70 years may well be explained by the fact that the risks of thromboembolic events and endometrial cancer from tamoxifen use are greater in postmenopausal women, 12 making the risk-benefit ratio for tamoxifen use in younger women more appealing.…”
Section: Discussionmentioning
confidence: 99%